2003
DOI: 10.1046/j.1365-2036.2003.01465.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactobacillus rhamnosus GG on ileal pouch inflammation and microbial flora

Abstract: SUMMARYBackground: Preliminary trials of probiotics in preventing recurrent chronic pouchitis have been encouraging. Aim: To investigate the efficacy of Lactobacillus GG supplementation as primary therapy for ileal pouch inflammation, and its effect on the microbial flora. Methods: Twenty patients, with a previous history of pouchitis and endoscopic inflammation, were recruited for a prospective, randomized, double-blind, placebocontrolled trial of Lactobacillus GG supplementation (10 LGG, 10 placebo) in two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
121
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(133 citation statements)
references
References 33 publications
3
121
0
4
Order By: Relevance
“…In addition, all patients relapsed within 3 months of stopping the probiotic [120]. Similar effects were observed after application of lactobacilli [121,122].…”
Section: Inflammatory Bowel Disease (Ibd)supporting
confidence: 67%
“…In addition, all patients relapsed within 3 months of stopping the probiotic [120]. Similar effects were observed after application of lactobacilli [121,122].…”
Section: Inflammatory Bowel Disease (Ibd)supporting
confidence: 67%
“…Recent studies have also shown that some bacterial strains or mixtures may have the capacity to promote or reduce intestinal inflammation (19,27). This evidence has led to an increased use of probiotic preparations in the therapy of IBD that usually contain lactobacilli, bifidobacteria, or Escherichia coli strains (8,14,18).…”
mentioning
confidence: 99%
“…One observational study of patients receiving LGG after pouch formation has reported a lower rate of pouchitis than in historical controls [72]. However, Kuisma et al have found no difference in mean pouchitis scores between placebo and LGG-treated groups at the end of a 3-month study period [73]. Finally, a reduction in endoscopic and clinical disease activity associated with an increase in faecal probiotic species has been demonstrated in 51 patients with pouchitis after surgery for UC who consumed fermented milk containing lactobacilli and bifidobacteria [74].…”
Section: Pouchitismentioning
confidence: 99%